2015
DOI: 10.1007/s11908-015-0489-2
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Leishmaniasis in Travellers: a Focus on Epidemiology and Treatment in 2015

Abstract: Imported cutaneous leishmaniasis (CL) is a growing problem with increasing global travel to endemic areas. Returned travellers seeking care encounter significant barriers to treatment, including diagnostic delays and difficult access to anti-leishmanial drugs. Treatment recommendations in non-endemic settings are a moving target, reflecting recent developments in Leishmania diagnostics and therapeutics. Accumulating experience with molecular-based species identification has enabled species-directed therapy. Cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 98 publications
0
20
0
1
Order By: Relevance
“…Eleven million people are infected by the Leishmania parasite worldwide, and 2 million new infections are reported annually [1]. Approximately 90 % of all Leishmania infections are cutaneous forms; they are characterized as multilocular, chronic or Peru and Bolivia [2]. During transmission, the sandflies inoculate the infective forms of Leishmania, named promastigotes, into the skin, and the dermal macrophages internalize them.…”
Section: Introductionmentioning
confidence: 99%
“…Eleven million people are infected by the Leishmania parasite worldwide, and 2 million new infections are reported annually [1]. Approximately 90 % of all Leishmania infections are cutaneous forms; they are characterized as multilocular, chronic or Peru and Bolivia [2]. During transmission, the sandflies inoculate the infective forms of Leishmania, named promastigotes, into the skin, and the dermal macrophages internalize them.…”
Section: Introductionmentioning
confidence: 99%
“…The average number of CL cases, which is 0.7-1.3 million per year, continues to increase rapidly in our country and all over the world due to the difficulties and inadequacies in the fight against the disease (4,5,7). This increases the importance of producing a protective vaccine against the disease, which is a serious public health problem (3,6,(31)(32)(33)(34)(35).…”
Section: Discussionmentioning
confidence: 99%
“…Studies showed that nanosilver cement has high antibacterial activity and high effectiveness against multi resistant bacteria without cytotoxicity in vitro. Recently, findings have demonstrated that nanosilver has anti-inflammatory effects and increases wound healing and dressings of wounds [1,2,37]. If these results are confirmed in vivo, nanosilver may be appropriate for ulcer treatment [1].…”
Section: Application Of Nano Drugs In Treatment Of Leishmaniasismentioning
confidence: 99%